THE IMPLEMENTATION OF FISHBONE STRATEGY TO IMPROVE THE STUDENTS’ ARGUMENTATIVE WRITING SKILL - ORIJA SIMANJUNTAK; TASYA SALSABILA PUTRI; YOSI AGNES PAKPAHAN (CV KULTURA DIGITAL MEDIA, 2022)
The aim of this research is that the researchers want to know, does the Fish bone strategy able to improve students’ writing ability in writing an Argumentative Text in grade X MIPA of SMA Negeri 3 Pematangsiantar. Indonesia context, writing is considered as difficult and hard activity indicating that oral culture is much better than writing one. The students’ works are sufficiently kept in the libraries, although to publish those is much more worthy. Therefore, it is necessary to improve the students’ writing skill trough a meaningful way namely by teaching writing skill through Fishbone Strategy.